Tinjauan Fiqh Muamalah terhadap Kontrak Pembiayaan Leasing pada Lembaga Pembiayaan Konsumen “X”: A Fiqh Muamalah Review of Leasing Financing Contracts at Consumer Finance Institution “X” - Muhammad Yusuf Nur Saifuddin; Fairuz Sabiq (Litera Academica Publishing, 2025)
The development of leasing financing as a means of meeting public needs has introduced new dynamics in modern economic transactions. However, conventional leasing practices raise debates regarding their compliance with the principles of fiqh muamalah, particularly in relation to the clarity of contracts, the fairness of rights and obligations, and the potential presence of gharar. This article aims to analyze leasing financing contracts at consumer finance institution “X” from the perspective of fiqh muamalah. This study employs a qualitative method with a juridical-empirical approach, utilizing contract document analysis and supporting interviews. The findings reveal that while leasing contracts formally fulfill contractual requirements, they do not fully conform to fiqh muamalah principles due to unclear contract structures and imbalanced risk allocation. The study concludes that clearer contract classification and the restructuring of contractual clauses are necessary to ensure justice and transparency. This research contributes to the development of contemporary fiqh muamalah studies and offers practical implications for improving leasing contracts in accordance with the principles of justice and public welfare.